Kontribusi Habaib dalam Perjuangan Kemerdekaan dan Perkembangan Pendidikan di Indonesia - Saefullah, Agus Susilo (AL-IBNOR, 2024)
This research examines Habaib contribution to two crucial aspects of Indonesian history: the struggle for independence and education development. The research method used is a historical approach and document analysis to investigate the role of Habib in supporting the struggle for independence and the development of education in Indonesia. The research results show that Habib, as a religious and intellectual figure, had a significant role in spreading the values ​​of justice, unity and courage during the struggle for independence. Apart from that, they also play an essential role in establishing madrasas and other Islamic educational institutions, which play a crucial role in the education progress in Indonesia. This research aims to understand Habaib contribution to forming a pluralist and civilized modern Indonesia. The implications of this research show that Habaib contribution was not only limited to the period of the independence struggle but also continued in the development of education in Indonesia. Their role in establishing and managing educational institutions has created a strong foundation for inclusive and progressive national education. This research suggests the need for greater recognition and appreciation for Habaib contribution to the history of the struggle for independence and education in Indonesia. Further research could focus on individual Habaib contributions and their impact on local communities. Apart from that, integrating the values ​​taught by Habaib into the national education curriculum can be a strategic step to strengthen the nation's character and identity.